Kemampuan Reagen Curcumax Mendeteksi Boraks dalam Bakso yang Direbus - Erna Dwi Astuti; Widagdo Sri Nugroho (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2017)
Borax is a harmful compound to human health but sometimes was used illegally as preservative in meatball. Curcumax reagent is a compound which developed from the previous borax detector base on tumeric extract. This reagen was developed as an easy kit to apply in the field. This study aims were to determine accuracy of sight obesrvation and spectrophotometer to detected borax in boiled meatballs which tested by Curcumax and to determine the effect of boiling on the borax presence in the meatballs. This study was using meatballs groupas a control and another meatballs group preserve with borax 0.5%. Each treatment group was boiled in 0, 5, 10, and 15 minutes and each treatment unit had three replications which consist five meatballs each of them. Boraxdetection was done by mixing 1ml Curcumax reagent into 1 ml meatball extract. Qualitative examination of borax presence in the meatballs was known based on the color changing of tested meatball’s extract from yellow became orange (direct sight with eyes). The Quantitaive analysis was done by measured using spectrophotometer base on wave-length (λ) at 570 nm. Data was analyzed with ANOVA and continued by Least Significant Difference (LSD) analysis. Borax detection using curcumax based on sight sense against color change giving an inconsistence result. Meanwhile quantitative measurement by spectrophotometer more accurate than one. Curcumax had been detected borax in meatball which boiled for 15 minutes.